Los estudios comparativos de hacienda y su importancia para la comprensión de la formación del Estado en Hispanoamérica en el siglo XIX - Fontana i Lázaro, Josep (2014)
Reflexion about the challenges historians interested in Public Budget confronts. The author introduces Antique Regime examples in order to make evidence the complexity of this subject of study. Finally, he refers to the significance these kinds of studies have to understand political and economical processes in post-independece Latin America.